An Electrolytic Zn–MnO2 Battery for High‐Voltage and Scalable Energy Storage. Issue 23 (2nd May 2019) - Chao, Dongliang; Zhou, Wanhai; Ye, Chao; Zhang, Qinghua; Chen, Yungui; Gu, Lin; Davey, Kenneth; Qiao, Shi‐Zhang
Abstract: Zinc‐based electrochemistry is attracting significant attention for practical energy storage owing to its uniqueness in terms of low cost and high safety. However, the grid‐scale application is plagued by limited output voltage and inadequate energy density when compared with more conventional Li‐ion batteries. Herein, we propose a latent high‐voltage MnO2 electrolysis process in a conventional Zn‐ion battery, and report a new electrolytic Zn–MnO2 system, via enabled proton and electron dynamics, that maximizes the electrolysis process. Compared with other Zn‐based electrochemical devices, this new electrolytic Zn–MnO2 battery has a record‐high output voltage of 1.95 V and an imposing gravimetric capacity of about 570 mAh g −1, together with a record energy density of approximately 409 Wh kg −1 when both anode and cathode active materials are taken into consideration. The cost was conservatively estimated at <US$ 10 per kWh. This result opens a new opportunity for the development of Zn‐based batteries, and should be of immediate benefit for low‐cost practical energy storage and grid‐scale applications. Abstract : High‐voltage and scalable energy storage was demonstrated for a new electrolytic Zn–MnO2 battery system. Because of the new mechanism of two‐electron electrolysis/electrodeposition of Zn/Zn 2+ and Mn 4+ /Mn 2+, the system displayed a record‐high output voltage (1.95 V) and energy density (ca. 409 Wh kg −1 ). In addition, the electrolysis process was modeled by DFT calculations.